2001
DOI: 10.1161/hq0901.095149
|View full text |Cite
|
Sign up to set email alerts
|

Relation of Blood Pressure Variability to Carotid Atherosclerosis and Carotid Artery and Left Ventricular Hypertrophy

Abstract: Abstract-The relationship of blood pressure (BP) variability to cardiovascular target-organ damage is controversial.Studies examining BP variability and left ventricular (LV) hypertrophy have been contradictory, and only limited data on the relation of BP variability to carotid atherosclerosis and carotid artery hypertrophy exist. BP variability was assessed as the standard deviation and coefficient of variation of awake and asleep pressures in 511 normotensive or untreated hypertensive subjects who underwent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0
2

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(39 citation statements)
references
References 37 publications
1
36
0
2
Order By: Relevance
“…Similar results (P40.2) were seen when a coefficient of variation (equal to the standard error divided by the mean of the 24-h measurements), which allows adjustment for the positive correlation between blood pressure mean values and variability, 5 was used in the analysis.…”
Section: Resultssupporting
confidence: 69%
See 3 more Smart Citations
“…Similar results (P40.2) were seen when a coefficient of variation (equal to the standard error divided by the mean of the 24-h measurements), which allows adjustment for the positive correlation between blood pressure mean values and variability, 5 was used in the analysis.…”
Section: Resultssupporting
confidence: 69%
“…Adult studies have assessed the variability of both systolic and diastolic blood pressure using measures such as the standard deviation of the daytime mean, 4,5,15 the standard deviation of the night time mean, 5,14 the coefficient of variation (estimated as the standard deviation divided by 100 times the mean blood pressure), 5 the difference between the average value in the top 5% of readings from the overall average for the individual, 4 intermittent standard deviations 6 and the sleep/awake ratio. 16 We used the standard deviation of the 24-h blood pressure monitoring values as a measure of the 24-h variability, which shows the spread of an individuals blood pressure readings taken over a 24-h period.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Conversely, in hypertensive Africans, left ventricular mass was significantly associated with office, 1-minute, 24-h, daytime and night time BP, as well as BP reactivity measurements, but there was a complete absence regarding the relationship with 24-h SBP variability. Schillaci et al 38 and Roman et al 43 also observed this lack of association in Caucasians with essential hypertension. Contradictory results have been provided over the years regarding the predictive value of BP variability, 4,8,10,14 which might be due to differences in methods, too few events or different indexes of BP variability.…”
Section: Discussionmentioning
confidence: 92%